Konsep Pendidikan Akhlak dalam Kitab Mau’izhatul Mu’minin Ihya Ulumuddin Karya Syaikh Muhammad Jamaluddin Al-Qasimi - Dirgahayu, Wini; Sumanti, Solihah Titin (Ikatan Dai Indonesia, 2025)
Moral education has an important role in shaping the character and personality of a Muslim. This research aims to analyze the concept of moral education in the book Mau'izhatul Mu'minin Ihya Ulumuddin, analyze the characteristics of noble morals, analyze methods of moral development, and examine its urgency in today's era. This research uses qualitative methods with the type of library research. The research results show that moral education according to Muhammad Jamaluddin Al-Qasimi includes three main dimensions, namely: morals towards Allah SWT, morals towards Rasulullah Saw, and morals towards fellow creatures. This concept emphasizes the integration of ethical behavior and spiritual values ​​based on the Al-Qur'an and Sunnah. Al-Qasimi also identified noble moral qualities such as tawakkal, tawadu, speaking kindly, and loving others as the moral foundation of Muslim individuals. Apart from that, methods of moral development that can be done include learning from wise teachers, hanging out with pious friends, and accepting other people's criticism with self-introspection, and he also emphasized the importance of continuous education in forming a strong moral character.